Diseño de identidad visual a través de estrategias de branding para el posicionamiento de licor artesanal “Don Vargas” en la ciudad de Baños de Agua Santa - Alvarez Peralvo, Tatiana Lizbeth (2023)
Ecuador has a wide variety of liquors, whether of artisanal or industrial origin. In the city of Baños de Agua Santa, a new artisan liquor is born, which does not have any type of element or graphic material to continue its production and marketing. Pretending to provide a solution, the present investigation was carried out, mentioning as an objective the design of the visual identity of this liquor exclusively for the city of Baños through a branding strategy, with this an own brand is established and helps to differentiate itself from similar products. Qualitative and quantitative research methods were applied, which helped to determine certain traits or attributes for the creation of the identity, with the results obtained, the brand development and its correct use, the user manual and a packaging prototype were established. Multimedia elements were designed for the augmented reality proposal so that people can interact with the product label and it becomes a value proposition, which is aligned with the branding strategy.